Prolactin Is Associated With Insulin Resistance and Beta-Cell Dysfunction in Infertile Women With Polycystic Ovary Syndrome - Yang, Haiyan; Lin, Jie; Li, He; Liu, Zhangwei; Chen, Xia; Chen, Qianqian (Frontiers in Endocrinology, 2021)
Background: Our study aimed to investigate if serum prolactin (PRL) levels associated with insulin resistance and β-cell dysfunction in infertile patients with polycystic ovary syndrome (PCOS). Methods: This was a retrospective cross-sectional study performed in a large Reproductive Medicine Center. From January 2007 to August 2018, a total of 792 PCOS and 700 non-PCOS infertile women were included. All patients’ prolactin levels were in the normal range. PCOS was diagnosed according to the Rotterdam Criteria. Anthropometric parameters, blood pressure, serum prolactin levels, sex hormones, fasting lipids, fasting plasma glucose (FPG), fasting insulin (FINS) and hepatic biological parameters were measured in all subjects. Results: Serum prolactin levels in PCOS women were significantly decreased compared with levels in non-PCOS women after adjusting for age and BMI (P < 0.05). Moreover, we found that prolactin levels were positively associated with high-density lipoprotein cholesterol (HDL-C) and negatively associated with age, BMI, waist circumference (WC), hip circumference (HC), luteinizing hormone/follicle stimulating hormone (LH/FSH), estradiol (E2), FINS, homeostasis model assessment of insulin resistance (HOMA-IR), homeostasis model assessment of β (HOMA-β), triglyceride (TG) and alanine aminotransferase (ALT) (P < 0.05). After adjusting for age and BMI, multiple linear regression analysis revealed that LH, LH/FSH, E2, FINS, HOMA-IR, and HOMA-β were negatively associated with serum PRL (P < 0.05). Conclusions: Low PRL levels within the normal range can predict the status of insulin resistance and β-cell dysfunction in infertile women with PCOS.